Caracterização funcional e estrutural de toxinas provenientes da peçonha da serpente Bothrops jararacussu e influência do varespladib - Êmylle Karoline Ramos Pinto (2023)
According to the World Health Organization, there are approximately 5.4 million snake bites each year, resulting in 2.7 million poisonings and 100.000 deaths. In Brazil, the genus Bothrops snakes are clinically relevant due to the frequency and severity of the accidents. Among the Bothrops snakes, the Bothrops jararacussu species stands out, whose venom is extensively studied and contains a high quantity of phospholipases A2 and related toxins, such as bothropstoxin I and II (BthTX-I and II). These toxins are responsible for the myotoxic effects observed after envenomation. Recently, varespladib (LY315920), a synthetic phospholipase A2 inhibitor, has shown promise as a candidate for neutralizing snake toxins. Therefore, the present study assessed the varespladib's ability to inhibit the BthTX-I toxicity through myographic and morphological studies using phrenic nerve-diaphragm muscle preparations from mice. The preparations were exposed to BthTX-I, varespladib, or the product of the pre-incubation of BthTX-I/varespladib. The results of this study indicate that varespladib can neutralize the paralytic and myotoxic effects of BthTX-I. Furthermore, the bioinformatics results (docking and molecular dynamics) suggest that varespladib, in addition to interacting with BthTX-I, may also establish interactions with BthTX-II. These interactions were observed both in the monomeric state of BthTX-II at neutral pH and in the dimeric state at acidic pH. Consequently, this evidence suggests a potential capacity for varespladib to inhibit the toxic effects of BthTX-II.